2017
DOI: 10.1097/md.0000000000008872
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic surgery assisted by colonoscopy for a submucosal cecal fecalith presenting as acute appendicitis

Abstract: Rationale:A cecal submucosal fecalith is extremely rare and is likely to be misdiagnosed as appendicitis with an incarcerated fecalith.Patient concerns:This review presents the case of a female patient complaining of recurrent abdominal pain in the right lower quadrant, similar to the clinical symptoms of appendicitis. Physical examination revealed an abdominal tenderness in the right lower quadrant without rebound tenderness or muscular tension. An ultrasound examination found a mass located in the right lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Alhalabi et al suggested that fecalith(s) could be trapped in the appendiceal orifice and develop in the submucosal layer over time [ 12 ]. Bustamante et al suggested that the result of long-term incarceration of an appendicular fecalith or the constant accumulation of feces through fissure(s) in the mucosa cause submucosal fecalith [ 15 , 18 ]. Ito et al favored the hypothesis that intussusception of the appendix, which excludes foreign bodies from the lumen of the appendix, may lead to submucosal fecalith.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Alhalabi et al suggested that fecalith(s) could be trapped in the appendiceal orifice and develop in the submucosal layer over time [ 12 ]. Bustamante et al suggested that the result of long-term incarceration of an appendicular fecalith or the constant accumulation of feces through fissure(s) in the mucosa cause submucosal fecalith [ 15 , 18 ]. Ito et al favored the hypothesis that intussusception of the appendix, which excludes foreign bodies from the lumen of the appendix, may lead to submucosal fecalith.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Kangaspunta et al demonstrated that preoperative abdominal CT was poor in detecting tumors in patients with acute appendicitis [20]. Since 1981, several studies have described submucosal fecalith(s) mimicking submucosal tumors, as shown in Table 1 [8][9][10][11][12][13][14][15][16][17][18]. Some characteristics of the 12 patients with submucosal fecalith included in our brief literature review included a mean age of 47 years (range, 6-74 years), a female-to-male prevalence ratio of 1:2, and the fecalith was located around the cecum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,35 Ruan et al reported a submucosal fecalith, not related to the cecal appendix, which lacked a mucosal ulcer in the wall of the cecum. 6…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Other reports have described appendiceal fecaliths discovered after surgical or endoscopic resections in symptomatic patients. [7][8][9][10][11] They are usually misidentified initially as a submucosal cecal or appendiceal tumor on the abdominal computed tomography scan or during colonoscopy and diagnosed as a fecalith postoperatively after resection due to concern for possible malignancy. 1,2,10 Appendiceal fecaliths are associated with acute appendicitis, intussusception of the appendix, or chronic right lower quadrant abdominal pain.…”
Section: Introductionmentioning
confidence: 99%